The affect theory reader. worldings, tensions, futures - Seigworth, Gregory J., 1961-; Pedwell, Carolyn (ANIMA (Duke University Press), 2023)
"Building on the foundational The Affect Theory Reader, this new volume gathers together contemporary scholarship that highlights and interrogates the contemporary state of affect inquiry. Unsettling what might be too readily taken-for-granted assumptions in affect theory, The Affect Theory Reader 2 extends and challenges how contemporary theories of affect intersect with a wide range of topics and fields that include Black studies, queer and trans theory, Indigenous cosmologies, feminist cultural analysis, psychoanalysis, and media ecologies. It foregrounds vital touchpoints for contemporary studies of affect, from the visceral elements of climate emergency and the sensorial sinews of networked media to the minor feelings entangled with listening, looking, thinking, writing, and teaching otherwise. Tracing affect's resonances with today's most critical debates, The Affect Theory Reader 2 will reorient and disorient readers to the past, present, and future potentials of affect theory."--